Effect of the stage of maturity and time-temperature frying conditions on the quality of banana chips, cavendish variety (Musa paradisiaca, var. Cavendishii) - Pena, Maria Theresa M.; De Leon, Sonia Y. (1982.)
Three stages of maturity, namely green, unripe: rare-ripe; and ripe, of the cavendish variety were used to determine their effect on the quality of banana chips produced. Objective analyses of the fruit reveal that the green, unripe stage was more suitable with a moisture content, percentage soluble solids and reducing sugars content lower than that or rare-ripe and ripe stages of maturity. With regard to the finished product, the chips from the unripe stage were lighter on color and had a lower moisture content than that of the latter stages. Statistical analyses show the banana chips from different stages of maturity were not significantly different in color, appearance, flavor but varied significantly in texture. Samples from the green, unripe stage were significantly different from the rest of the samples. The optimum time-temperature frying condition for cavendish banana chips was found to be 280°F for 2.5 minutes in the second frying. By subjective evaluation, the banana chips were described s brown to golden brown; oily to glossy; a slight to distinct banana chip flavor and a soft crisp texture. The panelists preferred the banana chips deep fat fried at 280°F for 5 minutes.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Banana chips